Factors influencing procurement procedure inTanzania prisons service - Lidenge, Amina Juma (2024)
A dissertation/Thesis submitted toMzumbe University as partial fulfillment of the requirement for the award of Degree of Master Business Administration in Corporate Management (MBA-CM) of Mzumbe University